Human Papillomavirus (HPV) and Pregnancy; Prevalence and Diagnostic Methods - Bozdayı, Gülendam; Dinç, Bedia; Rota, Seyyal; Biri, Aydan; Bayramoğlu, Özlem; Gürsoy, Rıfat (Gynecology Obstetrics & Reproductive Medicine, 2009)
OBJECTIVE: To investigate the prevalence of Human Papillomavirus (HPV) and type detection of Human Papillomavirus as the most important causative agent of cervical cancer by PCR in pregnant women applying to Obstetrics and Gynecology outpatient clinic in Gazi Hospital. MATERIAL AND METHOD: Two hundred asymptomatic pregnant women applying to Obstetrics and 102 asymptomatic women applying to Gynecology outpatient clinic were included. HPV DNA was extracted from cervical smear samples by using phenol chloroform isoamyl alcohol and amplified by MY09/11 primers. Specific primers were used for type 16/18 detection. RESULTS: Five (2.5%) of 200 pregnant women were HPV DNA (+), two (1%) of which were type 16,two (1%) of which were type 18 and one(0.5%) of which was type 11.Two(2%) of 102 women in contol group were positive, both of which were type 16. CONCLUSION: HPV prevalence in pregnant women is lower than indicated in the literature. The probable reason may be common monogamy in Turkey and the non-smoking, young patient profile with high social and economic level in our study group. However, asymptomatic but HPV positive patients were directed to clinicians for follow-up and treatment.